2015
DOI: 10.5271/sjweh.3544
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce sedentary behavior and increase physical activity during productive work: a systematic review

Abstract: Interventions to reduce sedentary behavior and increase physical activity during productive work: a systematic review by Commissaris DACM, Huysmans MA, Mathiassen SE, Srinivasan D, Koppes LLJ, Hendriksen IJM This systematic review on interventions intended to change workers' sedentary behavior or physical activity is the first to focus on initiatives that can be implemented during productive work and that change behavior while workers perform their usual jobs. Thus, the review offers decision support when sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
122
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 87 publications
4
122
0
3
Order By: Relevance
“…This finding is consistent with reviews that have found no negative impact of workplace sitting interventions on work performance [5456] or health [56] and is appropriate given the minimal nature of the interventions. However, changes in job performance, stress, and quality of life were inconclusive so more studies, with adequate power, are needed to corroborate these findings.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with reviews that have found no negative impact of workplace sitting interventions on work performance [5456] or health [56] and is appropriate given the minimal nature of the interventions. However, changes in job performance, stress, and quality of life were inconclusive so more studies, with adequate power, are needed to corroborate these findings.…”
Section: Discussionsupporting
confidence: 89%
“…For them, focusing on what to do to reduce sitting highlighted the reality that participants had little control over this behavior, and therefore it might be challenging for them to set achievable goals. Similar issues have been raised by several recent systematic reviews on interventions to change activity behavior [47-49]. They concluded that, although programs targeting physical activity or combined activity and sedentary behavior are effective at improving physical activity participation, only the ones that are designed to change sedentary behavior achieve the best results in reducing sitting time.…”
Section: Discussionmentioning
confidence: 59%
“…Given that women after menopause are at high risk of osteoporosis26 ) , physical activity promotion among middle-aged to older women would help to prevent this disease27 ) and contribute to healthy life span. Given the decreasing trend of energy expenditure at work28 ) and the high prevalence of no leisure-time exercise, workplace interventions for physical activity, including workstation interventions and promoting the use of stairs29 ) , may be a solution for maintaining or increasing regular physical activity level for Japanese workers.…”
Section: Discussionmentioning
confidence: 99%